Practical design and construction of solar ponds. (1st November 2022) - Meneses-Brassea, Bianca Paola; Perez, Annalisa; Golding, Peter
Highlights: Features, factors, and facets of solar pond design and construction. El Paso Solar Pond experience as the basis for design specifications. Design and planning ensure solar pond reliable and sustainable operation. Purpose of solar ponds provides focus for design and configuration. Abstract: Over the last four decades, salinity gradient solar pond (SGSP) science and technologies have advanced in practical projects. In this work, we show that understanding a salinity gradient solar pond's purpose provides the focus for preparing a preliminary design and physical configuration. This paper aims to share lessons learned in designing and constructing the El Paso Solar Pond. Features, factors, and facets of solar pond design and construction are presented straightforwardly to inform and guide planning for future work. Emphasis is on sodium chloride-based ponds, the base salt used for the El Paso Solar Pond. However, lessons learned are pertinent to additional salt source configurations. Reference to solar ponds operating in Australia and Israel provides design and construction insights. Careful design and planning prior to construction ensure the solar pond operates reliably and sustainably.